The Role of Ascorbic Acid in the Process of Azo Dye Degradation in Aqueous Solution - Adrianna Pach; Aleksandra Zaryczny; Agnieszka Podborska; Magdalena Luty-Błocho (Molecules, 2024)
In this work, the role of ascorbic acid in the process of azo dye degradation was explained. For this purpose, the kinetics of azo dye degradation under different conditions was studied. Among them, the influence of daylight protection/exposition, different concentrations of ascorbic acid (0.567–0.014 mol/dm3), and temperature (20 °C and 50 °C) on the rate of the dyes’ degradation was considered. For this process, the kinetic equation was proposed, which indicates that the process of azo dye degradation using ascorbic acid is first order. Moreover, the observed rate constants were determined, and the mechanism of azo dye degradation was proposed. Spectrophotometry results, together with FTIR, fluorescence spectroscopy, and DFT calculations, explain the origin of the decolorization of the azo dyes and highlight the role of ascorbic acid in this process. Detailed analysis of the obtained products indicates that the process itself goes through several stages in which equally or more toxic compounds are formed. Obtained results from LCMS studies indicate that during tropaeolin OO degradation, 1,2-Diphenylhydrazine (m/z 185.1073) is formed. Thus, the process of azo dye degradation should be carried out in protective conditions. The proposed mechanism suggests that ascorbic acid at high content levels can be used for azo dye degradation from aqueous solution and can be an alternative method for their removal/neutralization from waste solution but with caution during the process.